2019
DOI: 10.1111/dth.12975
|View full text |Cite
|
Sign up to set email alerts
|

The impact of omalizumab on quality of life and its predictors in patients with chronic spontaneous urticaria: Real‐life data

Abstract: Background Omalizumab is a third‐line treatment for chronic spontaneous urticaria (CSU). However, the real‐life data on the impact of omalizumab on CSU‐related quality of life (QoL) remain scarce. Objectives To investigate the impact of omalizumab on QoL and its predictors in CSU. A retrospective cohort study was done. The response to therapy was evaluated using urticaria activity score over 7 days (UAS7) and urticaria control test (UCT); the impairment in QoL was assessed using dermatology life quality index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
5
11
0
1
Order By: Relevance
“…But, we did not include these patients group in this study because we evaluated only standart OMA regime. 4,5,11,12 In line with the literature, this study found that the prevalence of CSU was higher in females. When males and females were compared in our study, the risk of relapse was not higher in female patients, as in the study by Marzano et al 13,14 In our study, 78% of the patients (39 patients) had complete remission at the end of 12 months.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…But, we did not include these patients group in this study because we evaluated only standart OMA regime. 4,5,11,12 In line with the literature, this study found that the prevalence of CSU was higher in females. When males and females were compared in our study, the risk of relapse was not higher in female patients, as in the study by Marzano et al 13,14 In our study, 78% of the patients (39 patients) had complete remission at the end of 12 months.…”
Section: Resultssupporting
confidence: 89%
“…Multiple factors may be involved in the clinical and prognostic polymorphism of CSU. [3][4][5] The guidelines for the treatment of CSU recommend the use of second-generation nonsedating H1-antihistamines for initial therapy and suggest up-dosing of these antihistamines up to 4-fold in patients with CSU who are unresponsive to standard doses. When they fail to achieve success, the guidelines recommend the use of omalizumab (OMA) as third-line therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the meta-analysis of real-life studies has shown a mean AE rate of 4% [14]. Moreover, the positive impact of omalizumab on various aspects of patient QoL has also been also demonstrated in clinical trials and real-life studies [41][42][43]. Yet, there are still some obscurities and challenges regarding the use of omalizumab for CSU.…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 99%
“…Less than 50% of patients with RA due to CSU achieve complete disease control and freedom of attacks with this [23]. Those who do not are recommended to treat with omalizumab, which benefits up 80% of them (see Table 2) [24].…”
Section: How To Control Mast Cell-mediated Recurrent Angioedema and Tmentioning
confidence: 99%